Managing the Impact of Resource Booms on the Real Effective Exchange Rate : The Role of Financial Sector Development. (IMF Working Papers; Working Paper, 2021)
Whereas most of the literature related to the so-called 'resource curse' tends to emphasize on institutional factors and public policies, in this research we focus on the role of the financial sector, which has been surprisingly overlooked. We find that countries that have financial systems with more depth, as well as those that actively manage their central banks' balance sheets experience less exchange-rate appreciation than countries that do not. We analyze the relationship between these two findings and suggest that they appear to follow separate mechanisms.